Main crops economic indicators analysis in the South-West Oltenia Region - Diana Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The agriculture is an important resource for South West Oltenia, with over 1 million hectares used for the cultivation of cereals (mainly maize and wheat), oil plants (especially sunflower), vegetables (tomatoes, cabbage, onions) and fruits (apples, watermelons, melons, grapes), potatoes, sugar beet, good quality wine production. In this study are analyzed indicators on the evolution of cultivated surfaces, yields and prices for main crops: the average annual rate of growth, deviations in absolute size. The research method used is quantitative analysis of statistical data series in 2007-2013. Using regression function we obtained trends of the indicators used.
Keywords: 330; production; prices; dynamics